Environmental Issues In Exploration Of Plastic Materials: A Studio Art Practice Research - Zhu, Xiaoming (2025)
The emergence of plastics has significantly enhanced daily convenience, but their large-scale production and use, driven by consumerism, have caused severe plastic pollution, straining the relationship between humans and nature. Despite efforts by environmentalists, scientists, and activists to raise awareness, scientific information alone often fails to change public perceptions due to a lack of vivid, emotionally engaging imagery of environmental issues. Art, however, uniquely conveys environmental information, offering perspectives that other disciplines cannot. While plastic pollution is a global crisis affecting both marine and terrestrial ecosystems, current artworks primarily focus on marine plastic pollution, overlooking the interconnectedness of plastic pollution and climate change. The absence of a theoretical foundation limits artists in fully exploring the potential of plastic materials for environmental themes. This research aims to examine and produce artworks through studio-based research by integrating eco-aesthetics, environmental issues, and overconsumption.